The effect of the COVID-19 pandemic on the quality of antenatal care services in Probolinggo District - Muthmainnah Zakiyyah; Stefanus Supriyanto; Ratna D. Wulandari; Tutik Ekasari; Umi Narsih (AOSIS, 2023)
Background: On March 11, 2020, the World Health Organization announced the status of a global pandemic for the 2019 coronavirus disease (COVID-19). Pregnant women are most vulnerable to being infected with COVID-19 and must take extra care of their health. The impact and risk of COVID-19 on pregnant and lactating women as well as on the fetus and baby are not yet known with certainty. However, due to changes in body shape and immune system, pregnant women are very susceptible to some respiratory infections. Objective: The purpose of this study was to determine the effect of the COVID-19 pandemic on the quality of antenatal care (ANC) services in Probolinggo Regency. Methods: This analytic research has a cross-sectional design. The participants are 326 pregnant women in the third trimester. Sampling uses simple random sampling. The sample is some pregnant women in the third trimester, as many as 179 people. Chi-square is used for analysis. Results: According to the study's findings, as many as 170 respondents did not confirm that they had COVID-19 (95%). 153 respondents were provided with quality ANC services (85%). Conclusion: The results of the statistical test obtained a value of P=0.09; so there is an influence during the COVID-19 pandemic on the quality of ANC services. Efforts that can be made are health workers limit meetings with pregnant women without reducing the quality of ANC services.